The Woman Role in Change Leadership - Al- Husban, Basma Khalaf (Journal of Economic, Administrative and Legal Sciences, 2021)
There is no doubt that great leaders are created step by step through a set of continuous processes that support and refine their capabilities, and accordingly we find that most studies have confirmed that the characteristics of women leaders are not sufficient alone in activating their roles as much as the surrounding environment should help in that. She plays a prominent role in strengthening the conditions for empowering women and providing the necessary conditions for her creativity, whether through her leadership roles or her regular roles, the study aims to identify the role that women play at the level of leading change in various areas of life, whether economic, political, social, and other other fields, by identifying the most prominent leadership characteristics and the skills that they should have, and an attempt to evaluate these different characteristics and capabilities and stand On the extent to which these characteristics contribute to leading the change process in general at any level of the state or different institutions, and the study also aimed to identify the most important methods and strategies that women use in leading change, and the effect of these strategies on their ability to lead change, and the study did not stop. Up to that point, it also sought to highlight the most important challenges facing women in societies, as well as to address the comparison of leadership style between men and women, by relying on the descriptive approach and the analytical method for the contribution of both approaches in the researcher’s point of view in achieving the basic purpose of this study, and the most prominent results were The study is that women have a prominent role in society in general, from their role in the family to their role in the highest leadership positions that take on Here, the study also proved that women have sufficient characteristics and qualities to qualify them to play a fundamental role in leading the process of change, and that they have the ability to carry out a set of different activities that lead towards change, whether those activities are related to the follow- up or development process and other activities that lead towards change on the one hand. The level of organizations and others, in addition to emphasizing that women are more cautious than men at the level of decision- making, but at the same time they are superior in terms of courage and ability to plan for the future, and in general, if women play a pivotal role in leadership, and therefore they can be described as fighting.